“Tradisi Manganan”: Sedekah Bumi dalam Masyarakat Bojonegoro, desa Dander dilihat dari Kebersyukuran: “Tradisi Manganan”: Sedekah Bumi dalam Masyarakat Bojonegoro, desa Dander dilihat dari Kebersyukuran - ARISTASARI, DEBY INDAH (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The tradition of manganan or earth alms is an annual tradition that is held once a year. This research is related to gratitude. Gratitude itself is a feeling of amazement and appreciation of the favors that have been obtained from the God to His servants, gratitude to others, and also to nature. This research aims to find out the description of gratitude in the manganan tradition in Dander Village, Bojonegoro. The researcher used the Interpretative Phenomenological Analysis (IPA) method. Researchers try to compile the results of literature review, interviews, and other supporting documentation. Things that are obtained is a description of gratitude in the manganan tradition. In addition, the researcher found a unique theme from the interview results, namely respecting the universe from the earth alms. From this, we can learn to respect the universe from the earth alms. learn to respect the surrounding nature. In addition, the earth alms itself is not only done by the Muslim community but can also be followed by non-Muslims.